DIGITAL LEARNING GAME “IMMUNITY” BERBASIS ANDROID - Ketut Gus Oka Ciptahadi; Sang Made Junindra Maha Arta (LPPM Universitas Dhyana Pura, 2022)
ABSTRACTThe immune system is the body's ability to fight infection, eliminating the work of toxins and other virulent factors that are antigenic and immunogenic. Currently, all efforts have been made through Communication, Information and Education (IEC) regarding information on how to increase the body's immune system to prevent contracting viral infections, and even if infected, the body will be strong against it. However, the delivery of information that is done by distributing information sheets or brochures whose contents are only in the form of text is less attractive to some people. So this is where the use of games to convey interactive and user friendly information will greatly contribute more so that information can be conveyed. Based on the discussion of the problem and previous research, in this study an Android-Based